1967
DOI: 10.1113/jphysiol.1967.sp008329
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of chylomicrons and albumin in dog kidney

Abstract: SUMMARY1. Under specified experimental conditions the distribution space of labelled chylomicrons in the kidney was 13-8 + 0 9 ml./100 g. tissue. The assumption is supported that this provides a measure for the quantity of intravascular plasma constituents.2. Values for red blood cells and albumin distribution spaces were 5*2 + 0-6 and 20*2 + 1 0 ml./100 g tissue, respectively, in the whole kidney.The ratio of tissue haematocrit over simultaneous arterial haematocrit averaged 0-56. The extravascular albumin fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Slotkoff and Lilienfield [1967] point out that the osmotic effect of the extravascular protein could be enhanced if it were to be broken down into smaller molecules by the enzymes present in the kidney. Pinter [1967] has suggested that the peculiar properties of mixtures of albumen and acid mucopolysaccharides in the interstitial tissues may contribute to a very high osmotic difference between the collecting ducts and the interstitium. The present investigation confirms that there is a large amount of extravascular albumen and the fact that the rapid protein leak probably takes place from the ascending vasa recta supports the idea of a form of counter-current mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slotkoff and Lilienfield [1967] point out that the osmotic effect of the extravascular protein could be enhanced if it were to be broken down into smaller molecules by the enzymes present in the kidney. Pinter [1967] has suggested that the peculiar properties of mixtures of albumen and acid mucopolysaccharides in the interstitial tissues may contribute to a very high osmotic difference between the collecting ducts and the interstitium. The present investigation confirms that there is a large amount of extravascular albumen and the fact that the rapid protein leak probably takes place from the ascending vasa recta supports the idea of a form of counter-current mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…They found a rapid loss of protein from post-glomerular vessels; 50 per cent of extravascular protein exchanged in 12 minutes -a very rapid rate of exchange compared to that of other organs. Pinter [1967], using isotope-labelled chylomicrons as an indicator of intravascular plasma space, found a large quantity of extravascular albumen in the kidney, equivalent to 31 per cent of the total renal albumen.…”
mentioning
confidence: 99%
“…One of these is the use of an intravascular tracer together with albumin (Pinter, 1967;Rasmussen, 1975). The other is allowing only a brief mixing time (about 1 min) for the tracer albumin, in order to confine the distribution volume to intravascular plasma (Gairtner, Vogel & Ulbrich, 1968;Rasmussen, 1974Rasmussen, , 1975.…”
Section: R Bell and Othersmentioning
confidence: 99%
“…In spite of these concentration differences, an increased flow of protein from the kidney does occur during mannitol diuresis, since the increase in lymph flow is proportionately greater than the decrease in protein concentration. This increased flow of protein could result either from a faster washout of the interstitial protein pool (14,15) or from an increased rate of protein extravasation; either might result from a change in renal hemodynamics.…”
Section: Figurementioning
confidence: 99%
“…Normal lymph-plasma ratios, on the other hand, raise the possibility that the medulla is not a significant source of renal lymph. From the functional standpoint, lack of a medullary lymphatic system would be surprising in view of the quantity of plasma proteins which leave the blood capillaries to enter the medullary interstitium (14)(15)(16). Although some studies show the failure of certain injection techniques to prove such a system (17,18), others have shown lymphatic vessels ascending from the papilla through inner and outer medulla to the arcuate collecting vessels (19).…”
mentioning
confidence: 99%